LEGAL PERSPECTIVES ON DIGITALISING LAND CERTIFICATES: Analyzing Synchronization and Harmonization in Indonesia’s Job Creation Law - Permadi, Iwan; Maharani, Diah Pawestri; Ahmad, Md Yazid (Jurisdictie: Jurnal Hukum dan Syariah, 2024)
This research explores the legal implications of land certificate digitalization under Indonesia's Job Creation Omnibus Law, focusing on the synchronization and harmonization of related regulations. The main question examines how the transition from traditional paper-based certificates to electronic titles (e-titles) can align with Indonesia's legal framework. The study is intended to analyze primary legal challenges and compare the Indonesian experience with Rwanda's successful e-title system. The paper employs a normative-juridical method, examining legal materials, including Electronic Information and Transactions Law and government regulations regarding land registration. The research discusses the synchronization of these laws and their application in ensuring data security, legal certainty, and efficient land governance. The result of the discussion highlights that while digitalizing land certificates can improve service delivery and efficiency, successful implementation is contingent upon the careful alignment of various laws and coordination between the National Land Agency and other government bodies. The comparative analysis with Rwanda’s e-title system offers useful insights into addressing potential legal and administrative challenges in Indonesia's digital transformation of land administration. This research contributes to offering actionable insights for policymakers aiming to modernize land governance in Indonesia. Penelitian ini mengkaji implikasi hukum digitalisasi sertifikat tanah berdasarkan UU Cipta Kerja, dengan fokus pada sinkronisasi dan harmonisasi peraturan perundang-undangan terkait. Fokus utama penelitian ini adalah untuk menganalisis tentang bagaimana transisi sertifikat tanah dalam bentuk kertas menjadi sertifikat tanah elektronik (e-title) dapat diselaraskan dengan kerangka hukum Indonesia yang ada. Penelitian ini diposisikan untuk menganalisis tantangan hukum utama dan membandingkan pengalaman Indonesa dengan sistem e-title di Rwanda yang dianggap berhasil. Paper ini akan mengkaji isu hukum ini dengan menggunakan metode yuridis normatif, yakni menganalisis berbagai bahan hukum peraturan perundangan-undangan, antara lain Undang-Undang Informasi dan Transaksi Elektronik, dan Peraturan Pemerintah yang terkait dengan pendaftaran tanah. Penelitian ini membahas sinkronisasi beberapa peraturan dan penerapannya dalam memastikan keamanan data, kepastian hukum, dan tata kelola pertanahan yang efisien. Hasil utama dari diskusi pada paper ini menyoroti bahwa meskipun digitalisasi sertifikat tanah dapat meningkatkan penyediaan layanan dan efisiensi, implementasi yang sukses bergantung pada penyelarasan berbagai undang-undang dan koordinasi yang cermat antara Badan Pertanahan Nasional dan badan pemerintah lainnya. Analisis komparatif dengan sistem e-title Rwanda menawarkan wawasan yang berguna untuk mengatasi potensi tantangan hukum dan administratif dalam transformasi digital administrasi pertanahan Indonesia. Penelitian ini memberikan kontribusi wawasan praktis bagi pembuat kebijakan yang bertujuan memodernisasi tata kelola pertanahan di Indonesia.